Gender, Politics, and the State, and the Māori - Houkamau, Carla (The Wiley Blackwell Encyclopedia of Gender and Sexuality Studies, 2016)
A diversity of perspectives and wide variety of cultural and social features characterize Māori society and there is no one consensus view held by Māori in relation to gender roles, political orientations, or Māori/government (or state) relations. Both Māori women and men have shared in the struggle to assert Māori resistance to colonial encroachment and one gender cannot be elevated over the other. Moreover, Māori views and perspectives on the different roles of Māori men and women are contested and differ tribally and between individuals. This entry describes aspects of precolonial Māori society that shaped traditional values and discusses key sociohistorical factors shaping gender roles among Māori. A focus on the contribution of Māori women to Māori development and advancement is offered. The relationship between Māori identity, culture, and the New Zealand government (or state) is highlighted throughout.
Keywords: crown policy; cultural practices; gender; identity; mana wāhine

Chapter 1: Reclaiming Māori education - Walker, Ranginui (Decolonisation in Aotearoa: Education, research and practice, 2016)
Keywords: assimilation; colonisation; education

Tribal data sovereignty: Whakatōhea rights and interests - Maui Hudson; Dickie Farrar; Lesley McLean (Indigenous Data Sovereignty, 2016)
The vast array of activities that tribal organisations in Aotearoa/New Zealand are responsible for illustrates the importance of high-quality information to support their decision-making. Tribal information needs encompass a broad range of domains, types of information and processes for management. This chapter examines the growingiwi(tribal) interest in data and their uses in the context of oneiwi, Te Whakatōhea, to explore howiwiare beginning to conceptualise their rights and interests over data in Aotearoa/New Zealand. It is focused on the Whakatōhea Māori Trust Board and how it is collecting and becoming the steward for a range of
Keywords: data sovereignty; iwi sovereignty; tino rangatiratanga

Māori wards and advisory boards - Bargh, Maria (Local Government in New Zealand: Challenges & Choices, 2016)
Local government in New Zealand faces major challenges. Among the most pressing are continual legislative change, threats to its autonomy, the gradual erosion of community voices in council planning and decision-making, and the need for funding solutions to ensure property rates remain affordable. As well, there is an urgent need for a more coordinated approach across central government on major policy issues such as climate change and housing. This book exposes these challenges and proposes and debates solutions for the future of our local government. Strong local government is vital for ensuring economic growth across and within regions and local communities, for enhancing community wellbeing, for funding and providing the infrastructure needed for, in some cases, rapidly growing and diverse communities, for ensuring our environment is valued and protected, and for planning for development in a time of constraint on resources. This book is a 'one-stop information shop' on local government that can be used by those who regularly interact with or study this area of government, by those working within local authorities, and by those who actively work to ensure their communities grow in a sustainable way.
Keywords: local government